Comparison of trophic niche and digestive enzymes of four species of catfishes of the Punarbhaba River in India - Gupta, Subhasree Sen; Homechoudhury, Sumit (Indian Journal of Fisheries, 2012)
The feeding ecology and digestive enzyme profile of four species of catfishes namely, Eutropiichthys vacha Hamilton, 1822;Ailia coila Hamilton, 1822; Neotropius atherinoides Bloch, 1794 and Pangasius pangasius Hamilton, 1822, belonging tothe order Siluriformes were collected from Punarbhaba River. Stomach content of the fishes were analyzed to determinetrophic diversity, niche breadth of each fish species as well as to calculate relative abundance in natural habitat and index ofrelative importance (IRI) of different prey items in fish diet. Digestive enzyme profile has also been studied by characterizationof amylase, invertase, cellulase, pepsin, alkaline protease and non-specific esterase from fish liver, stomach and intestine.Among the four fishes, E. vacha is found to be a generalist in terms of trophic behaviour whereas A. coila and N. atherinoidesare specialists having higher IRI value for plankter and P. pangasius showing malacovory. The food niche segregation isfound to be incomplete. The digestive enzyme profile was also found to vary from species to species in order to supportfeeding habit.